1986
DOI: 10.1177/001979398603900409
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Earnings of Vietnam and Korean-Era Veterans

Abstract: Using Current Population Survey data for 1967 and 1979, this paper compares the earnings of Vietnam veterans to those of Korean veterans (in both cases, relative to nonveterans) at similar points in their work lives-twelve to sixteen years after their discharge. In both 1967 and 1979, the unadjusted average annual earnings of veterans and nonveterans were similar. But an analysis that controls for such factors as education, age, race, and( marital status shows that Vietnam veterans were worse off than their no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 3 publications
0
20
0
Order By: Relevance
“…They found only small overall differences (a 2 percent gap) between the earnings of Vietnam-era veterans and similar individuals who never served, and, as in previous studies, they found that only those with less than a high school education realized benefits from veteran status. Schwartz (1986) recently contributed to this literature by using CPS data for 1967 and 1979 to compare the earnings of Vietnam veterans to nonveterans and Korean veterans to nonveterans at similar points in their post-military work lives. He found that whereas Korean-era veterans were economically indistinguishable from nonveterans, Vietnam veterans had a significantly lower rate of return per year of education than their nonveteran counterparts.…”
Section: Previous Studiesmentioning
confidence: 99%
“…They found only small overall differences (a 2 percent gap) between the earnings of Vietnam-era veterans and similar individuals who never served, and, as in previous studies, they found that only those with less than a high school education realized benefits from veteran status. Schwartz (1986) recently contributed to this literature by using CPS data for 1967 and 1979 to compare the earnings of Vietnam veterans to nonveterans and Korean veterans to nonveterans at similar points in their post-military work lives. He found that whereas Korean-era veterans were economically indistinguishable from nonveterans, Vietnam veterans had a significantly lower rate of return per year of education than their nonveteran counterparts.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Considerable discussion exists in the literature in an attempt to explain the observed differences between veterans and non-veterans. This has ranged from the more basic human capital arguments (Cohen, Segal and Temme, 1992;Goldberg and Warner, 1986;Berger and Hirsch, 1983;Cooper, 1981;Danzon, 1980;DeTray, 1982;Little and Fredland, 1979;Norrblum, 1977 ) to the more complex notions that involve the bridging hypothesis (Xie, 1992;Schwartz, 1986;Berger and Hirsch, 1985;Fredland and Little, 1983 ) regarding military service.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there exists a substantial volume of empirical work looking into the correlation and interaction between veteran status and observed differences in both the earnings and employment status of the male population. This work can be broadly categorized as focusing either on testing the hypothesis that military service and training are factors contributing to the stock of human capital for veterans (Cohen, Segal and Temme, 1992;Goldberg and Warner, 1986;Berger and Hirsch, 1983;Cooper, 1981;Danzon, 1980;DeTray, 1982;Fredland and Little, 1979;Norrblum, 1977) or testing the hypothesis that military service acts as a bridge so that veterans have access to more favorable labor market conditions after discharge from the military (Xie, 1992;Schwartz, 1986;Berger and Hirsch, 1985;Fredland and Little, 1983). From any of these past investigations, irrespec-tive of the focus, the resulting outcome looked at either veteran and non-veteran differences, black-white veteran differences or veterans' differences based upon the time period of active duty military service.…”
Section: Previous Evidencementioning
confidence: 99%
“…Earlier research finds Vietnam-era veterans tended to be worse off than comparable non-veterans and veterans from the WWII and Korean Wars in terms of income, employment, and job prestige (Card, 1983; Rothbart, Sloan, & Joyce, 1981; Schwartz, 1986). For example, Schwartz (1986) compares the earnings of Vietnam and Korean veterans twelve to sixteen years after their discharge and finds the rate of return per year of education was significantly lower for Vietnam veterans than Korean veterans, who were economically indistinguishable from their nonveteran contemporaries.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier research finds Vietnam-era veterans tended to be worse off than comparable non-veterans and veterans from the WWII and Korean Wars in terms of income, employment, and job prestige (Card, 1983; Rothbart, Sloan, & Joyce, 1981; Schwartz, 1986). For example, Schwartz (1986) compares the earnings of Vietnam and Korean veterans twelve to sixteen years after their discharge and finds the rate of return per year of education was significantly lower for Vietnam veterans than Korean veterans, who were economically indistinguishable from their nonveteran contemporaries. Similarly, cross-sectional comparisons show WWII veterans had higher earnings than comparable nonveterans (Berger & Hirsch, 1983; Rosen & Taubman, 1982), though this premium disappears and WWII veterans actually appear to have earned less than comparable nonveterans when nonrandom selection into the military is accounted for using instrumental variable methods (Angrist & Krueger, 1994).…”
Section: Introductionmentioning
confidence: 99%